Utilising consumer reviews for passive surveillance of foodborne illnesses: insights and challenges from the Indian restaurant - Prabhune, Akash; Hari, Vinay Sri; Sethiya, Neeraj Kumar; Gauniyal, Mansi (Intelektual Pustaka Media Utama, 2025)
This study explores the feasibility of leveraging consumer reviews for passive surveillance of foodborne illnesses, drawing parallels with pharmacovigilance systems. Utilizing a mixed-methods approach, including a literature review, qualitative interviews with key stakeholders, and quantitative analysis of 56,000 restaurant reviews using a bidirectional encoder representation from transformers (BERT-based) aspect-based sentiment analysis model, the study seeks to understand the potential of social media data in enhancing food safety regulations. Despite the promise shown by the aspect-based analysis in identifying hygiene-related concerns, challenges such as data reliability, language diversity, and the absence of verifiable evidence limit the direct application of consumer reviews for regulatory purposes. Key informants highlighted the need for a tailored surveillance system, considering the Indian restaurant industry’s diversity and scale. The quantitative analysis revealed hygiene concerns in a significant portion of reviews, yet the specificity and verifiability of these complaints remain issues. The study suggests a cautious yet optimistic approach towards integrating social media data into foodborne illness surveillance, emphasizing the enhancement of traditional reporting mechanisms, targeted awareness campaigns, and industry collaboration. The findings advocate for a comprehensive strategy that includes developing a common platform for stakeholder communication and strengthening policy frameworks to support a collaborative surveillance system, particularly in developing contexts like India.